Minimizing Manufacturing Industry Capital Costs through Governance, Corporate Risk Management, Social Responsibility and Company Size - Rofiqah Wahdah; Anwar Sanusi; Prihat Assih (Trescode Green Organization, 2024)
This research aims to analyze the influence of corporate governance, corporate risk management, corporate social responsibility, and company size on the cost of capital in the manufacturing industry listed on the Indonesia Stock Exchange. This research design is quantitative, with samples taken using non-random techniques, such as purposive sampling or judgment sampling, so that the total research sample is 45 companies, with a research period of 4 years and a total of 180 research data. The data analysis technique uses panel data with path analysis. The research results show that implementing broad and integrated corporate risk management reduces the cost of capital. Large company size can increase the cost of capital in manufacturing industrial companies listed on the Indonesian Stock Exchange. Meanwhile, the implementation of corporate governance and corporate social responsibility does not reduce the company's capital cost. Future advice is that company management is expected to pay more attention to management practices related to corporate social responsibility, corporate risk management, and capital costs because these factors impact increasing the value and survival of the company in the future. Management also needs to pay attention to the role of capital costs, which can mediate the implementation of corporate risk management in increasing company value.